PENEGAKAN PROVINCE OF ALL MANKIND DALAM KOMERSIALISASI ANTARIKSA - Pasaribu, Mia Gisella Kartika; Tanggono, Sandy (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The development of space law under the Space Agenda 2030 has undergone numerous phases and evaluations. Human rights are an inseparable part of international law that must be upheld. Space law and human rights must operate synergistically within a treaty. The need for a treaty to guarantee legal certainty within the limits of commercial activities in outer space is also part of the human rights concerns of space law. The commercialization of outer space has binding regulations, which can then give rise to potential human rights violations, particularly from the perspective of business competition by developing countries and/or environmental threats to human life. These issues should be the focus of space law, allowing for the creation of laws to fill the gaps and establish independent enforcement and oversight instruments for space activities. The Space Agenda 2030 is expected to serve as a forum for the international community to address issues affecting commercial space activities, leading to the creation of space law that effectively prioritizes human rights.